Faktor yang mempengaruhi pembangunan kerjaya pekerja sokongan di Jabatan Penyiaran Sarawak - Edie Rahmat, bin Salleh. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
ABSTRACT FACTORS INFLUENCING CAREER DEVELOPMENT OF SUPPORT WORKERS ATJABATAN PENYIARAN SARA WAf( Edie Rahmat bin Salleh The purpose of this research is to determine the factors that influencing in career development of support workers at Jabatan Penyiaran Sarawak (RTM) Kuching. As that, the study involved the entire respondent from the company. A total of50 respondents were selected as a sample from whole ofthe support workers. The methods used in this study were by distributed questionnaires to the respondent as main way to collected information needed. Respondent need to fill in the questionnaires distributed in a period time was given. The questionnaire included three section which is section A, section Band section C. Section A is almost related about respondents demography, section B is about career development scope and section C is factors that influenced career development. The result of the finding was analyzed by using statistic descriptive and inference statistic. The statistic descriptive method was used to measure the distribution of respondent demography as gender, age, length of services and level of education. Meanwhile, the inference statistic that included T-Test, One Way ANOVA and Pearson Correlation was used to test the null hypothesis in this study. From the result it show that factors such as management support, job fit, training and development and supervisor and supervision influencing in career development at Jabatan Penyiaran Sarawak (RTM), Kuching because it show a significant relationship among all variable was tested. However factors gender, age, length of services and level of education did not show the difference significant of influencing career development ofsupport workers.